Preparation process of battery

By constructing a structure with P-type layer on the upper and N-type layers on the lower in Cu2O thin-film solar cells, and performing P-type doping on the back surface of the cuprous oxide thin film, the back interface carrier recombination problem is solved, and the photovoltaic and electrical properties of the solar cells are improved.

CN120282561APending Publication Date: 2025-07-08LONGI GREEN ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311843518.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2025-07-08

AI Technical Summary

Technical Problem

In existing Cu2O thin-film solar cells, the carrier recombination rate at the back interface is high, resulting in a decrease in charge traps and carrier mobility, affecting device performance.

Method used

By forming an N-type layer on the substrate, then forming a cuprous oxide thin film light-absorbing layer and doping Group V elements, and then forming a P-type layer on top, a battery structure with the P-type layer on top and the N-type layer on bottom, and P-type doping is performed on the back surface of the cuprous oxide thin film to form a strong P-type back surface field to suppress electron and hole recombination.

Benefits of technology

Effectively promote hole transmission to the back electrode, prevent electron transmission to the back electrode, reduce carrier recombination, significantly improve the filling factor, short-circuit current and open-circuit voltage of solar cells, and improve photovoltaic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004639800840000171
    Figure BDA0004639800840000171
  • Figure HDA0004639800990000011
    Figure HDA0004639800990000011
Patent Text Reader

Abstract

The invention provides a cuprous oxide thin film battery and a preparation method thereof. The preparation method comprises the steps of substrate preparation, electron transport layer preparation, cuprous oxide light absorption layer preparation, light absorption layer doping, hole transport layer preparation, electrode preparation and the like. Wherein the light absorption layer is doped by V-group elements from the surface of one side, far away from the electron transmission layer, of the cuprous oxide film, and specifically, the doping depth during doping accounts for 20-50% of the thickness of the cuprous oxide film. According to the method provided by the invention, a strong P-type back surface electric field at the cuprous oxide interface can be realized, the hole carrier extraction efficiency of the cuprous oxide solar cell is effectively improved, and the photovoltaic performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of solar cells, and particularly to a cuprous oxide thin film solar cell and its preparation process. Background Art

[0002] With the continuous increase in energy consumption, the demand for cheap and efficient solar cells is also growing. Cuprous oxide (Cu2O) is a p-type semiconductor with a high absorption coefficient of >104 / cm. Its band gap width is 2.2 eV, and it can directly utilize visible light with wavelengths of 300 - 600 nm in sunlight. Based on the theoretical photoelectric conversion efficiency of Cu2O thin film solar cells, it can reach 20%. Moreover, since the spectral sensitivity overlap between Cu2O and Si is relatively small, it has great potential for realizing high-efficiency tandem solar cells. At the same time, Cu and O elements are widely present on the earth, and the raw materials are extremely easy to obtain, and the production cost of Cu2O thin film solar cells is also relatively low. Therefore, Cu2O has been considered by industry insiders as a semiconductor thin film material for third-generation solar cells.

[0003] However, some studies have shown that the effective carrier diffusion length of Cu2O thin films exceeds the thickness of the thin films, and the carrier recombination at the back interface of Cu2O thin films will have an important impact on the device performance. Therefore, for Cu2O thin film solar cells, selective carrier extraction and interface passivation at the back interface are the keys to obtaining high-efficiency devices. Currently, there is a technology that uses nitrogen-doped Cu2O prepared by an electrochemical deposition process as the hole transport layer of the thin film battery, but an interface will be generated between it and the Cu2O light absorption layer thin film due to discontinuous deposition, resulting in charge traps, increasing the recombination rate of electrons and holes, and reducing the carrier mobility of the material. Summary of the Invention

[0004] To solve the problems in the above technology, the preparation method of the cuprous oxide thin film battery provided in this application forms an N-type layer on a substrate, forms a cuprous oxide thin film light absorption layer on the N-type layer, dopes the cuprous oxide thin film with group V elements, and then forms a P-type layer on the doped cuprous oxide thin film, which can achieve interface-free doping and obtain a cuprous oxide thin film battery with the N-type layer at the bottom and the P-type layer at the top, effectively improving the photovoltaic performance of the battery. The specific technical solution of this application is as follows:

[0005] A preparation method of a cuprous oxide thin film battery, which includes the following steps:

[0006] Substrate preparation;

[0007] Preparation of the electron transport layer, which includes forming an electron transport layer thin film on the substrate;

[0008] Preparation of the light absorption layer, which includes forming a cuprous oxide thin film on the electron transport layer;

[0009] Doping of the light-absorbing layer, which includes doping the cuprous oxide thin film with Group V elements;

[0010] Preparation of the hole transport layer, which includes forming a hole transport layer on the doped cuprous oxide thin film;

[0011] Preparation of the electrode, which includes preparing an electrode on the hole transport layer.

[0012] Further, the substrate preparation includes preparing an FTO substrate.

[0013] Further, in the preparation of the electron transport layer and the hole transport layer, ALD, PVD or PEALD methods can be used for thin film deposition.

[0014] Further, the electron transport layer material is selected from gallium oxide, titanium oxide, zinc oxide or tin oxide, and / or the hole transport layer material is selected from tin oxide, preferably antimony-doped tin oxide.

[0015] Preferably, the electron transport layer is a gallium oxide thin film. More preferably, by using the ALD method, trimethylgallium (TMGa) is used as the gallium source, water is used as the oxygen source, and Ar gas is used as the carrier gas to deposit a gallium oxide layer thin film with a thickness of 5 - 50 nm.

[0016] Preferably, the hole transport layer is a p-type SnO2 thin film. More preferably, by using the magnetron sputtering method with an Sb-doped SnO2 target as the target material, Ar and O2 as the sputtering source gases, a p-type SnO2 thin film with a thickness of 5 nm to 200 μm is deposited.

[0017] Further, the preparation of the light-absorbing layer includes: using a copper target as the target material and depositing a cuprous oxide thin film with a thickness of 800 nm - 5 μm by magnetron sputtering.

[0018] Further, the radio frequency power supply for the magnetron sputtering is 13.56 MHz, the deposition power is 200 W, the sputtering source gases are Ar and O2, the Ar flow rate is 100 sccm, the O2 flow rate is 7.2 sccm, the substrate temperature is 100 °C, and the reaction time is 60 - 300 min.

[0019] Further, the doping of the light-absorbing layer is to dope Group V elements on the surface of the cuprous oxide thin film away from the electron transport layer side.

[0020] More preferably, the percentage of the doping depth of the Group V elements during doping in the thickness of the cuprous oxide thin film is 20 - 50%.

[0021] Further, the doping of the light-absorbing layer includes using thermal diffusion for doping Group V elements.

[0022] Further, the thermal diffusion includes gas thermal diffusion or chemical solution immersion thermal diffusion.

[0023] Further preferably, nitrogen or phosphorus element doping is carried out by using the gas thermal diffusion; or arsenic, antimony or bismuth element doping is carried out by using the chemical solution immersion thermal diffusion.

[0024] Further, when nitrogen element doping is carried out by using the gas thermal diffusion, the flow rate of doped nitrogen gas is 30 - 180 sccm, and the doping concentration is 0.1 at% - 20 at%.

[0025] Further, when phosphorus element doping is carried out by using the gas thermal diffusion, 50 - 300 mg of phosphorus powder forms phosphorus vapor to react with the cuprous oxide film.

[0026] Further, when nitrogen or phosphorus element doping is carried out by using the gas thermal diffusion, argon gas with a flow rate of 80 sccm is added as a carrier gas during the doping reaction process.

[0027] Further, the diffusion pressure of argon gas is maintained at 100 - 400 Pa during the doping reaction.

[0028] Further, when nitrogen or phosphorus element doping is carried out by using the gas thermal diffusion, the diffusion temperature is 200 - 600 °C, the temperature gradient is 50 - 100 °C, and the diffusion time is 30 - 85 min.

[0029] Further, when nitrogen or phosphorus element doping is carried out by using the gas thermal diffusion, the reaction system is heated to the diffusion temperature at a rate of 10 °C per minute.

[0030] Further, after the diffusion is completed, the argon gas is turned off, and the reaction system is cooled to 100 °C at a rate of 10 °C per minute, and then naturally cooled to room temperature.

[0031] Further, when arsenic, antimony or bismuth element doping is carried out by using the chemical solution immersion thermal diffusion, the cuprous oxide film is immersed in an arsenic source, antimony source or bismuth source solution, and after contact and reaction, annealing is carried out.

[0032] Further, the arsenic source solution is arsenic nitrate solution. Further preferably, the concentration of the arsenic nitrate solution is 0.2 - 2 M.

[0033] Further, the antimony source solution is potassium antimonyl tartrate solution. Further preferably, the concentration of the potassium antimonyl tartrate solution is 0.01 - 0.2 M.

[0034] Further, the bismuth source solution is bismuth nitrate solution. Further preferably, the concentration of the bismuth nitrate solution is 0.2 - 2 M.

[0035] Further, when doping with arsenic, antimony or bismuth elements by using the chemical solution immersion thermal diffusion, the reaction time is 10 s - 10 min.

[0036] Further, when doping with arsenic, antimony or bismuth elements by using the chemical solution immersion thermal diffusion, the annealing temperature is 200 - 500 °C, and the annealing time is 30 s - 20 min.

[0037] Further, the electrode preparation includes preparing a conductive electrode by using a magnetron sputtering method or an ALD method, and the electrode is selected from IZO, ITO, IWO, ITiO or AZO.

[0038] This application also relates to the following technical solutions:

[0039] A cuprous oxide thin film battery, the battery includes: a substrate, an electron transport layer, a cuprous oxide light absorption layer, a hole transport layer and an electrode which are arranged in sequence, wherein, the cuprous oxide light absorption layer is doped with group V elements.

[0040] Further, a partial area on one side of the cuprous oxide light absorption layer close to the hole transport layer is doped with group V elements.

[0041] More preferably, the percentage of the doping depth in the thickness of the cuprous oxide light absorption layer is 20 - 50%.

[0042] Further, the thickness of the electron transport layer is 5 - 50 nm, the thickness of the cuprous oxide light absorption layer is 800 nm - 5 μm, and the thickness of the hole transport layer is 5 nm - 200 nm.

[0043] Further, the electron transport layer material is selected from gallium oxide, titanium oxide, zinc oxide or tin oxide, preferably gallium oxide, and the hole transport layer material is selected from tin oxide, preferably antimony-doped tin oxide.

[0044] Further, the cuprous oxide thin film battery is prepared by the preparation method described in any one of the above.

[0045] The above description is only an overview of the technical solutions of this application. In order to make the technical means of this application clearer and to the extent that those skilled in the art can implement it according to the content of the specification, and in order to make the above and other purposes, features and advantages of this application more obvious and understandable, the following takes the specific implementation manners of this application as examples for illustration. Brief Description of the Drawings

[0046] Figure 1 It is a schematic diagram of the device structure of a Cu2O thin film solar cell provided by this application.

[0047] Among them, 1 is the IZO electrode layer, 2 is the P-type SnO2 layer, 3 is the cuprous oxide layer, 4 is the N-type gallium oxide layer, 5 is the FTO layer, and 6 is the glass substrate Specific embodiments

[0048] The following embodiments of the present application are only used to illustrate the specific implementation manners of the present application, and these embodiments should not be construed as limiting the present application. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present application are regarded as equivalent replacement manners and fall within the protection scope of the present application.

[0049] The present application provides a method for preparing a cuprous oxide thin film battery, which includes the following steps:

[0050] Substrate preparation;

[0051] Preparation of the electron transport layer, which includes depositing an electron transport layer thin film on the substrate;

[0052] Preparation of the light-absorbing layer, which includes depositing a cuprous oxide thin film on the electron transport layer;

[0053] Doping of the light-absorbing layer, which includes doping the cuprous oxide thin film with group V elements;

[0054] Preparation of the hole transport layer, which includes depositing a hole transport layer on the doped cuprous oxide thin film;

[0055] Electrode preparation, which includes preparing an electrode on the hole transport layer.

[0056] Conventional cuprous oxide thin film batteries have a structure with the P-type layer (hole transport layer) at the bottom and the N-type layer (electron transport layer) at the top. There is often a problem that electrons in the N-type layer are transported to the electrode on the P-type layer side, resulting in easy recombination of photo-generated carriers and affecting the device performance. In the technical solution of the present application, the battery structure is adjusted to an inverted structure with the P-type layer at the top and the N-type layer at the bottom, and a cuprous oxide thin film is set as the light-absorbing layer between the P-type layer and the N-type layer to realize P-type doping treatment on the back surface of the cuprous oxide thin film (in the present application, the back surface is the surface of the cuprous oxide thin film in contact with the hole transport layer). The battery structure prepared by the process of the present application can introduce an additional hole concentration at the cuprous oxide interface, reduce the back surface potential, effectively promote the transport of holes to the back electrode, prevent the transport of electrons to the back electrode, and thus inhibit the recombination of electrons and holes on the back surface, and can significantly improve the fill factor, short-circuit current, and open-circuit voltage of the cuprous oxide thin film solar cell. And this direct doping method on the cuprous oxide thin film does not introduce an additional layer structure, so there will be no defect of additional carrier recombination loss caused by the interface generated due to material discontinuity.

[0057] In an embodiment of the present application, the substrate is a conductive glass. In a specific embodiment, the substrate is fluorine-doped tin dioxide conductive glass (FTO). In some other embodiments, the substrate may be ITO.

[0058] In a specific embodiment, the substrate is processed before use. In a specific embodiment, an FTO substrate of 2.5 cm × 2.5 cm is selected and ultrasonically cleaned with acetone, absolute ethanol, and deionized water in sequence for 10 - 20 min, and then dried with nitrogen for standby.

[0059] In an embodiment of the present application, the preparation of the electron transport layer includes depositing an electron transport layer on the previously prepared FTO substrate.

[0060] In a specific embodiment, the electron transport layer can be prepared by ALD, PVD, or PEALD method.

[0061] In a specific embodiment, the electron transport layer material is selected from gallium oxide, titanium oxide, zinc oxide, or tin oxide.

[0062] In some other specific embodiments, the electron transport layer material is selected from Nb2O5, SrTiO3, BaSnO3, In2O3, and WOx.

[0063] In a preferred embodiment, a gallium oxide layer is prepared as the electron transport layer by using an ALD device.

[0064] In a specific embodiment, trimethylgallium (TMGa) is used as the gallium source, water is used as the oxygen source, and Ar gas is used as the carrier gas, and the preparation is carried out by an alternating pulse deposition growth method.

[0065] In a specific embodiment, one deposition cycle consists of four processes: introducing the TMGa source for 0.1 s; purging with Ar for 5 s; introducing H2O gas for 20 s; purging with Ar for 5 s. 200 deposition cycles are carried out to complete the deposition of the gallium oxide thin film.

[0066] In a specific embodiment, the thickness of the electron transport layer is 5 - 50 nm.

[0067] In a preferred embodiment, the thickness of the electron transport layer is 10 - 30 nm.

[0068] In an embodiment of the present application, the preparation step of the light-absorbing layer includes depositing a cuprous oxide thin film layer on the electron transport layer.

[0069] In a specific embodiment, a copper target is used as the target, and a cuprous oxide thin film with a thickness of 800 nm to 5 μm is deposited by magnetron sputtering.

[0070] In some preferred embodiments, the operating parameters of magnetron sputtering can be set as follows: the radio frequency power supply is 13.56 MHz, the deposition power is 200 W, the sputtering source gases are Ar and O2, the Ar flow rate is 100 sccm, the O2 flow rate is 7.2 sccm, the substrate temperature is 100 °C, the reaction time is 60 - 300 min, preferably 100 - 150 min.

[0071] In some other specific embodiments, the cuprous oxide thin film can be prepared by chemical deposition method, electrochemical deposition method or thermal oxidation method. This application does not limit this, and those skilled in the art can select a suitable method according to actual needs.

[0072] In a specific embodiment, the thickness of the cuprous oxide thin film is 800 nm - 5 μm. In some preferred embodiments, the thickness is 1.5 - 4 μm.

[0073] In a specific embodiment of this application, group V element doping is carried out to a certain depth from the back surface of the cuprous oxide into the cuprous oxide thin film. In a specific embodiment, the percentage of the doping depth of the group V element doping in the thickness of the cuprous oxide thin film is 20 - 50%. The doping depth described in this application refers to the extension length from the film surface into the film interior.

[0074] By carrying out group V element doping to a certain depth in the cuprous oxide thin film, it can be achieved that the part of the cuprous oxide thin film close to the electron transport layer has a low hole concentration, inhibiting the recombination of electrons and holes on the back surface, and the part close to the hole transport layer has a high hole concentration, introducing an additional hole concentration between the interface of the cuprous oxide thin film and the hole transport layer, thereby obtaining a high-efficiency cuprous oxide solar cell. Further setting the diffusion depth to a percentage of the cuprous oxide thin film thickness of 20 - 50% can optimize the above effects.

[0075] In an embodiment of this application, the cuprous oxide thin film is further doped with group V elements by thermal diffusion method.

[0076] The doping or improvement methods in the prior art cannot well solve the problems of interface carrier recombination and transport. The technical solution of this application proposes a new preparation process, which uses thermal diffusion method to carry out controllable-depth group V element doping (replacing the position of O) on the cuprous oxide light-absorbing layer, can introduce an additional hole concentration on the back surface of the cuprous oxide light-absorbing layer, effectively promote the transport of holes to the back electrode, inhibit the recombination of electrons and holes on the back surface, and this method will not form an additional interface to cause charge traps or affect electron transport characteristics.

[0077] The thermal diffusion process is a high-temperature surface modification technology. When the ambient temperature rises, the atomic thermal motion of the substrate material intensifies, causing some atoms to leave their original lattice positions after obtaining sufficiently high energy and becoming interstitial atoms, while generating a large number of lattice vacancies. Impurity elements can migrate to the vacancies to achieve doping. The advantages of the thermal diffusion process mainly lie in: on the one hand, uniform doping on the surface can be realized, that is, the doped impurity atoms are usually relatively uniformly distributed laterally on the surface, which helps to ensure that the electronic properties of the material remain consistent throughout the device; on the other hand, the doping depth can be adjusted, that is, during the thermal diffusion doping process, the doping depth of impurity atoms can be precisely controlled by controlling parameters such as temperature, time, and atmosphere to meet different application requirements. In the specific implementation manner of this application, a certain depth of heavy doping of group V elements is implemented on the back surface of cuprous oxide (in this application, the back surface is the surface on the side where cuprous oxide contacts the hole transport layer) to replace the position of O in the original lattice, so as to form a strong P-type back surface field on the back surface of cuprous oxide, repel minority carriers from moving towards the back interface, reduce the recombination of minority carriers on the back surface, and thus improve the photovoltaic performance.

[0078] In the implementation manner of this application, according to the different forms of elements during the doping process, the thermal diffusion method includes the gas thermal diffusion method (applicable to gaseous doping elements) and the chemical solution immersion thermal diffusion method (applicable to liquid doping elements). Using the thermal diffusion method for surface doping will not affect the overall structure and properties of the material, and at the same time, the type and properties of the doping elements can be precisely controlled according to requirements, so as to achieve precise regulation of the material characteristics.

[0079] In some specific implementation manners, the cuprous oxide thin film is doped with nitrogen or phosphorus elements by the gas diffusion method.

[0080] In the specific implementation manner, based on the cuprous oxide interface, gas thermal diffusion nitrogen doping is carried out, and the concentration of doped N2 is 0.1 at% - 20 at% (the concentration refers to the atomic ratio of N to O in cuprous oxide). In a preferred implementation manner, the doping concentration is 8 - 15 at%.

[0081] In a specific embodiment, the N2 flow rate is set at 30 - 180 sccm to control the nitrogen doping amount. In a preferred embodiment, the flow rate is 90 - 150 sccm. After the internal working pressure of the quartz tube is pumped down to 2 - 10 Pa, the tube furnace is heated to the diffusion temperature of 200 - 600 °C, preferably 300 - 500 °C, at a rate of 10 °C per minute, and the temperature gradient is 50 - 100 °C. Argon is injected into the quartz tube as a carrier gas (which can drive the movement of N vapor) at a flow rate of 80 sccm, and the argon diffusion pressure is maintained within the range of 100 - 400 Pa for 30 min - 85 min. Argon can play a role in transporting the doping gas to the target area in this case. By adjusting the pressure of argon, the transport speed and diffusion speed of the doping gas during the diffusion process can also be controlled. In a preferred embodiment, the argon diffusion pressure is 200 - 300 Pa, and the holding time is 40 - 60 min. After the thermal diffusion process is completed, the argon and nitrogen are turned off, and the tube furnace simultaneously starts to cool down to 100 °C at a rate of 10 °C per minute, and then cools naturally to room temperature. Throughout the thermal diffusion process and the cooling process, the quartz tube is kept under evacuation until the tube furnace reaches room temperature.

[0082] In a specific embodiment, gas thermal diffusion phosphorus doping is carried out based on the copper oxide interface. The specific operation is as follows: along the gas flow direction, phosphorus powder and the sample to be doped are sequentially placed in the quartz boat, with 50 - 300 mg of phosphorus powder added to form phosphorus vapor at the diffusion temperature. The quartz boat is located in the middle of the quartz tube and the tube furnace. After the internal working pressure of the quartz tube is pumped down to 2 - 10 Pa, the tube furnace is heated to the diffusion temperature (200 - 600 °C) at a rate of 10 °C per minute, and the temperature gradient is 50 - 100 °C. Argon is injected into the quartz tube as a carrier gas (driving the movement of P vapor) at a flow rate of 120 sccm, and the argon diffusion pressure is maintained within the range of 200 - 400 Pa for 30 min - 85 min. After the thermal diffusion process is completed, the argon is turned off, and the tube furnace simultaneously starts to cool down to 100 °C at a rate of 10 °C per minute, and then cools naturally to room temperature. Throughout the thermal diffusion process and the cooling process, the quartz tube is kept under evacuation until the tube furnace reaches room temperature.

[0083] In some other specific embodiments, chemical solution immersion thermal diffusion method is used to dope elements such as arsenic, antimony or bismuth into the copper oxide thin film.

[0084] In a specific embodiment, the copper oxide thin film to be doped is immersed in an arsenic source, antimony source or bismuth source solution, and after sufficient reaction for a certain time, annealing is carried out.

[0085] In a specific embodiment, the arsenic source solution can be arsenic nitrate solution. In a specific embodiment, the concentration of the arsenic nitrate solution is 0.2 - 2 M.

[0086] In a specific embodiment, the antimony source solution may be a potassium antimonyl tartrate solution. In a specific embodiment, the concentration of the potassium antimonyl tartrate solution is 0.01 - 0.2 M.

[0087] In a specific embodiment, the bismuth source solution is a bismuth nitrate solution. In a specific embodiment, the concentration of the bismuth nitrate solution is 0.2 - 2 M.

[0088] In a specific embodiment, in the chemical solution immersion thermal diffusion method, the immersion time is 10 s - 10 min. Preferably, the annealing temperature is 200 - 500 °C, and the annealing time is 30 s - 20 min.

[0089] In a specific embodiment, the Cu2O thin film is immersed in a solution containing As for surface As element doping to improve its p-type performance, increase the hole concentration, and improve the conductivity.

[0090] In a specific embodiment, the following operations can be adopted: Select arsenic nitrate as the arsenic source and perform the operation in a glove box under a N2 atmosphere. Immerse the sample to be treated in the above solution to ensure full contact between the Cu2O thin film layer and the solution. To explore the best treatment effect, it is necessary to strictly control the immersion time in the above solution. In a preferred embodiment, the immersion time is 10 s - 10 min. After immersion, in order to ensure successful doping of As element, a thermal annealing treatment is carried out. The annealing temperature is 50 - 500 °C, and the annealing time is 30 s - 20 min, thus obtaining a Cu2O light absorption layer doped with As.

[0091] In a specific embodiment, the Cu2O thin film is immersed in a solution containing Sb for surface Sb element doping to improve its p-type performance, increase the hole concentration, and improve the conductivity.

[0092] In a specific embodiment, the following operations can be adopted: Select potassium antimonyl tartrate as the antimony source, dissolve it in deionized water, and stir for 10 min - 50 min. After complete dissolution, immerse the sample to be treated in the above solution to ensure full contact between the Cu2O thin film layer and the solution. To explore the best treatment effect, it is necessary to strictly control the immersion time in the above solution. In a preferred embodiment, the immersion time is 10 s - 10 min. After immersion, in order to ensure successful doping of Sb element, a thermal annealing treatment is carried out. The annealing temperature is 200 - 500 °C, and the annealing time is 30 s - 20 min, thus obtaining a Cu2O light absorption layer doped with Sb.

[0093] In a specific embodiment, the Cu2O thin film is immersed in a solution containing Bi for surface Bi element doping to improve its p-type performance, increase the hole concentration, and improve the conductivity.

[0094] In a specific embodiment, the following operations can be adopted: Select bismuth nitrate as the bismuth source, immerse the sample to be processed in the above solution to ensure sufficient contact between the Cu2O thin film layer and the solution. To explore the best treatment effect, it is necessary to strictly control the immersion time in the above solution. In a preferred embodiment, the immersion time is 10 s - 10 min. After immersion, in order to ensure successful doping of Bi element, thermal annealing treatment is carried out. The annealing temperature is 200 - 500 °C, and the annealing time is 30 s - 20 min, thus obtaining a Bi-doped Cu2O light absorption layer.

[0095] In the embodiment of the present application, the preparation steps of the hole transport layer include depositing a P-type SnO2 thin film on the surface of the above-mentioned doped cuprous oxide.

[0096] In a specific embodiment, using an Sb-doped SnO2 target as the target material, a P-type SnO2 thin film with a thickness of 5 nm - 200 μm is deposited on the cuprous oxide thin film by magnetron sputtering. In a preferred embodiment, the thickness is 50 - 150 nm.

[0097] In a preferred embodiment, the radio frequency power supply for the magnetron sputtering is 13.56 MHz, the deposition power is 100 W, the sputtering source gases are Ar and O2, the Ar flow rate is 60 sccm, the O2 flow rate is 3 sccm, and the reaction time is 60 - 300 min.

[0098] In some other specific embodiments, the SnO2 thin film can be prepared by chemical deposition method, electrochemical deposition method or thermal oxidation method. The present application does not limit this, and those skilled in the art can select a suitable method according to actual needs.

[0099] In the embodiment of the present application, the electrode preparation method can be selected from magnetron sputtering method, ALD method or other conventional methods in the art. In a specific embodiment, the electrode can be selected from IZO, ITO, IWO, ITiO or AZO.

[0100] In a specific embodiment, the thickness of the electrode film layer is 40 - 100 nm.

[0101] The present application also provides the following technical solutions:

[0102] A cuprous oxide thin film battery, the structure of the battery includes: a conductive glass substrate, an electron transport layer, a cuprous oxide light absorption layer, a hole transport layer and an electrode arranged in sequence, wherein the cuprous oxide light absorption layer is doped with a Group V element.

[0103] In a specific embodiment, a partial area on the side of the cuprous oxide light absorption layer close to the hole transport layer is doped with a Group V element.

[0104] In a specific embodiment, the partial region doped with group V elements means that doping with a controllable depth is performed on the surface of the light absorption layer, and after doping, the cuprous oxide light absorption layer is doped with group V elements only within a certain doping depth range on the surface.

[0105] In a specific embodiment, the percentage of the doping depth of the cuprous oxide light absorption layer doped with group V elements in the thickness of the cuprous oxide thin film is 20 - 50%.

[0106] In a specific embodiment, the partial region doped with group V elements means that doping with a controllable depth is performed on the surface of the light absorption layer by using the thermal diffusion method provided in this application.

[0107] In a specific embodiment, the thickness of the electron transport layer is 5 - 50 nm, the thickness of the cuprous oxide light absorption layer is 800 nm to 5 μm, and the thickness of the hole transport layer is 5 nm - 200 nm.

[0108] In a specific embodiment, the material of the electron transport layer is selected from gallium oxide, titanium oxide, zinc oxide or tin oxide, and preferably gallium oxide.

[0109] In a specific embodiment, the material of the hole transport layer is selected from tin oxide, and preferably antimony - doped tin oxide.

[0110] In a specific embodiment, the cuprous oxide thin - film battery is prepared by the above - mentioned preparation method provided in this application.

[0111] The cuprous oxide thin - film battery and its preparation method involved in the technical solution of this application, through a specific battery device structure (the P - type layer is on the top, the N - type layer is on the bottom, and a cuprous oxide thin - film light absorption layer is arranged between the P - type layer and the N - type layer) and a preparation process of performing P - type doping on the back surface of the cuprous oxide thin film, can introduce an additional hole concentration at the cuprous oxide interface, reduce the back - surface potential, effectively promote the hole transfer to the back electrode, prevent the electron transfer to the back electrode, and further inhibit the recombination of electrons and holes on the back surface, and can significantly improve the fill factor, short - circuit current and open - circuit voltage of the cuprous oxide thin - film solar cell. And this way of directly doping on the cuprous oxide thin film does not introduce an additional layer structure, so there will be no defect of additional carrier recombination loss caused by the interface generated due to material discontinuity. This specific battery structure and processing technology of this application can effectively improve the photovoltaic performance and electrical performance of the cuprous oxide thin - film battery, and has significant technical effects.

[0112] Example

[0113] Unless otherwise specified, the experimental methods used below are all conventional methods.

[0114] The materials, reagents, etc. used below can be obtained commercially without special instructions.

[0115] Example 1

[0116] Prepare an N-doped Cu2O thin film battery in the following steps:

[0117] (1) Ultrasonically clean a 2.5 cm × 2.5 cm FTO substrate with acetone, absolute ethanol, and deionized water in sequence for 10 - 20 min, and dry it with nitrogen.

[0118] (2) Prepare a gallium oxide layer using an ALD device. Trimethylgallium (TMGa) is used as the gallium source, water is used as the oxygen source, and Ar gas is used as the carrier gas. The growth mode of alternating pulse deposition is adopted. One deposition cycle consists of four processes: introducing the TMGa source for 0.1 s, purging with Ar for 5 s, introducing H2O gas for 20 s, and finally purging with Ar for 5 s. A total of 200 times are completed for film deposition, and the film thickness is 20 nm.

[0119] (3) Prepare a cuprous oxide light-absorbing layer using reactive sputtering. Use a copper target as the target material, a 13.56 MHz radio frequency power supply, select a deposition power of 200 W, introduce Ar and O2 during sputtering, with flow rates of 100 sccm and 7.2 sccm respectively, keep the substrate temperature at 100 °C, sputter for 120 min, and the film thickness is 3.5 μm.

[0120] (4) Perform N doping on the cuprous oxide thin film obtained in step (3), with a doping concentration of 12 at%. The nitrogen gas flow rate is 120 sccm. After evacuating the internal working pressure of the quartz tube to 2 - 10 Pa, heat the tube furnace to the diffusion temperature of 400 °C at a rate of 10 °C per minute. Inject argon gas as the carrier gas into the quartz tube at a flow rate of 80 sccm, and keep the diffusion pressure within the range of 250 Pa for 50 min. After the thermal diffusion process ends, turn off the argon gas and nitrogen gas, and the tube furnace starts to cool down to 100 °C at a rate of 10 °C per minute, and then naturally cools to room temperature. The quartz tube is kept in a pumping state until the tube furnace reaches room temperature. The doping depth is 1.2 μm.

[0121] (5) Prepare p-type Sb:SnO2 using a sputtering device. The target material is an Sb-doped SnO2 target (Sb2O3:SnO2 = 2:8), use a 13.56 MHz radio frequency power supply, select a deposition power of 100 W, select Ar and O2 as the sputtering sources, with flow rates of 60 sccm and 3 sccm respectively. The sputtering time is 30 min, and the film thickness is 100 nm.

[0122] (6) The IZO electrode is prepared by sputtering method. A 13.56 MHz RF power supply is used, and the deposition power is selected as 100 W. Ar and O2 are introduced during the sputtering process, with flow rates of 60 sccm and 5 sccm respectively. The sputtering time is 30 min, and the film thickness is 70 nm. Thus, the N-doped Cu2O thin film battery is obtained.

[0123] Example 2

[0124] The P-doped Cu2O thin film battery is prepared by the following steps:

[0125] (1) The 2.5 cm × 2.5 cm FTO substrate is ultrasonically cleaned with acetone, absolute ethanol, and deionized water in sequence for 10 - 20 min, and then dried with nitrogen.

[0126] (2) The gallium oxide layer is prepared by an ALD device. Trimethylgallium (TMGa) is used as the gallium source, water is used as the oxygen source, and Ar gas is used as the carrier gas. The growth mode of alternating pulse deposition is adopted. One deposition cycle consists of four processes: introducing the TMGa source for 0.1 s, Ar purge for 5 s, introducing H2O gas for 20 s, and finally Ar purge for 5 s. A total of 200 times are completed for film deposition, and the film thickness is 20 nm.

[0127] (3) The cuprous oxide light-absorbing layer is prepared by reactive sputtering method. A copper target is used as the target material, a 13.56 MHz RF power supply is used, and the deposition power is selected as 200 W. Ar and O2 are introduced during the sputtering process, with flow rates of 100 sccm and 7.2 sccm respectively. The substrate temperature is maintained at 100 °C, the sputtering time is 120 min, and the film thickness is 3.5 μm.

[0128] (4) The cuprous oxide thin film obtained in step (3) is P-doped. The specific operation is as follows: Along the gas flow direction, 200 mg of P powder and the sample prepared in the previous step are placed in the quartz boat in sequence. The quartz boat is in the middle of the quartz tube and the tube furnace. After evacuating the internal working pressure of the quartz tube to 2 - 10 Pa, the tube furnace is heated to the diffusion temperature of 400 °C at a rate of 10 °C per minute. Argon gas is injected into the quartz tube as the carrier gas at a flow rate of 120 sccm, and the diffusion pressure is maintained within 250 Pa for 50 min. After the thermal diffusion process is completed, the argon gas is turned off, and the tube furnace starts to cool down to 100 °C at a rate of 10 °C per minute, and then naturally cools to room temperature. The quartz tube is kept in a pumping state until the tube furnace reaches room temperature. The doping depth is 1 μm.

[0129] (5) Prepare p-type Sb:SnO2 using a sputtering device. The target is an Sb-doped SnO2 target (Sb2O3:SnO2 = 2:8). Use a 13.56 MHz RF power supply, select a deposition power of 100 W, and select Ar and O2 as the sputtering sources with flow rates of 60 sccm and 3 sccm respectively. The sputtering time is 30 min, and the film thickness is 100 nm.

[0130] (6) Prepare the IZO electrode by sputtering. Use a 13.56 MHz RF power supply, select a deposition power of 100 W, and introduce Ar and O2 during the sputtering process with flow rates of 60 sccm and 5 sccm respectively. The sputtering time is 30 min, and the film thickness is 70 nm. Thus, the N-doped Cu2O thin film battery is obtained.

[0131] Example 3

[0132] Prepare the Sb-doped Cu2O thin film battery in the following steps:

[0133] (1) Ultrasonically clean a 2.5 cm × 2.5 cm FTO substrate with acetone, absolute ethanol, and deionized water in sequence for 10 - 20 min, and dry it with nitrogen.

[0134] (2) Prepare the gallium oxide layer using an ALD device. Trimethylgallium (TMGa) is used as the gallium source, water is used as the oxygen source, and Ar gas is used as the carrier gas. Adopt an alternating pulse deposition growth mode. One deposition cycle consists of four processes: introducing the TMGa source for 0.1 s, Ar purge for 5 s, introducing H2O gas for 20 s, and finally Ar purge for 5 s. A total of 200 times are completed for film deposition, and the film thickness is 20 nm.

[0135] (3) Prepare the cuprous oxide light absorption layer by reactive sputtering. Use a copper target as the target, a 13.56 MHz RF power supply, select a deposition power of 200 W, introduce Ar and O2 during the sputtering process with flow rates of 100 sccm and 7.2 sccm respectively, keep the substrate temperature at 100 °C, the sputtering time is 120 min, and the film thickness is 3.5 μm.

[0136] (4) Dope the cuprous oxide thin film obtained in step (3) with Sb. The specific operation is to use potassium antimonyl tartrate as the Sb source, dissolve it in deionized water, stir for 30 min. After sufficient dissolution, immerse the sample prepared in the previous step in the above solution to ensure full contact between the sample and the solution. The duration is 5 min. Then perform thermal annealing for 10 min at a temperature of 300 °C to obtain the Sb-doped Cu2O light absorption layer. The doping depth is 1.5 μm.

[0137] (5) The p-type Sb:SnO2 is prepared by a sputtering device. The target is an Sb-doped SnO2 target (Sb2O3:SnO2 = 2:8). A 13.56 MHz RF power supply is used, the deposition power is selected as 100 W, the sputtering sources are Ar and O2, and the flow rates are 60 sccm and 3 sccm respectively. The sputtering time is 30 min, and the film thickness is 100 nm.

[0138] (6) The IZO electrode is prepared by sputtering. A 13.56 MHz RF power supply is used, the deposition power is selected as 100 W, and Ar and O2 are introduced during the sputtering process, with flow rates of 60 sccm and 5 sccm respectively. The sputtering time is 30 min, and the film thickness is 70 nm. Thus, the N-doped Cu2O thin film battery is obtained.

[0139] Example 4

[0140] The N-doped Cu2O thin film battery is prepared by the following steps:

[0141] (1) The 2.5 cm × 2.5 cm FTO substrate is ultrasonically cleaned with acetone, absolute ethanol, and deionized water in sequence for 10 - 20 min, and then dried with nitrogen.

[0142] (2) The gallium oxide layer is prepared by an ALD device. Trimethylgallium (TMGa) is used as the gallium source, water is used as the oxygen source, and Ar gas is used as the carrier gas. The alternating pulse deposition growth mode is adopted. One deposition cycle consists of four processes: introducing the TMGa source for 0.1 s; Ar purging for 5 s; introducing H2O gas for 20 s; and finally Ar purging for 5 s. A total of 200 times are completed for film deposition, and the film thickness is 20 nm.

[0143] (3) The cuprous oxide light-absorbing layer is prepared by reactive sputtering. Using a copper target as the target, a 13.56 MHz RF power supply is used, the deposition power is selected as 200 W, and Ar and O2 are introduced during the sputtering process, with flow rates of 100 sccm and 7.2 sccm respectively. The substrate temperature is maintained at 100 °C, the sputtering time is 120 min, and the film thickness is 3.5 μm.

[0144] (4) The cuprous oxide thin film obtained in step (3) is N-doped, with a doping concentration of 25 at%, and the nitrogen flow rate is 220 sccm. After the internal working pressure of the quartz tube is pumped to 2 - 10 Pa, the tube furnace is heated to the diffusion temperature of 400 °C at a rate of 10 °C per minute. Argon is injected into the quartz tube as the carrier gas at a flow rate of 80 sccm, and the diffusion pressure is maintained within 250 Pa for 50 min. After the thermal diffusion process ends, the argon and nitrogen are turned off, and the tube furnace starts to cool down to 100 °C at a rate of 10 °C per minute, and then naturally cools to room temperature. The quartz tube is kept under pumping until the tube furnace reaches room temperature. The doping depth is 3.5 μm.

[0145] (5) Prepare p-type Sb:SnO2 using a sputtering device. The target is an Sb-doped SnO2 target (Sb2O3:SnO2 = 2:8). Use a 13.56 MHz RF power supply, select a deposition power of 100 W, select Ar and O2 as the sputtering sources, with flow rates of 60 sccm and 3 sccm respectively. The sputtering time is 30 min, and the film thickness is 100 nm.

[0146] (6) Prepare the IZO electrode using the sputtering method. Use a 13.56 MHz RF power supply, select a deposition power of 100 W, and introduce Ar and O2 during the sputtering process, with flow rates of 60 sccm and 5 sccm respectively. The sputtering time is 30 min, and the film thickness is 70 nm. Thus, the N-doped Cu2O thin film battery is obtained.

[0147] Comparative Example 1

[0148] Prepare the Cu2O thin film battery through the following steps:

[0149] (1) Clean the substrate: Ultrasonically clean a 2.5 cm × 2.5 cm FTO substrate with acetone, absolute ethanol, and deionized water in sequence for 10 - 20 min, and dry it with nitrogen at room temperature.

[0150] (2) Deposit the hole transport layer: Prepare p-type Sb:SnO2 using a sputtering device. The target is an Sb-doped SnO2 target (Sb2O3:SnO2 = 2:8); use a 13.56 MHz RF power supply, with a deposition power of 100 W, introduce Ar at 60 sccm and O2 at 3 sccm during the sputtering process. The sputtering time is 30 min, and the film thickness is 100 nm;

[0151] (3) Deposit the p-type cuprous oxide layer: Prepare the cuprous oxide layer using reactive sputtering. The target is a copper target, use a 13.56 MHz RF power supply, with a deposition power of 200 W, introduce Ar at 100 sccm and O2 at 7.2 sccm during the sputtering process, and keep the substrate temperature at 100 °C. The sputtering time is 120 min, and the film thickness is 3.5 um;

[0152] (4) Deposit the electron transport layer: Prepare the gallium oxide layer using an ALD device, trimethylgallium (TMGa) as the gallium source, water as the oxygen source, and Ar gas as the carrier gas. Use an alternating pulse deposition growth method. One deposition cycle consists of four processes: introducing the TMGa source for 0.1 s; purging with Ar for 5 s; introducing H2O gas for 20 s; and finally purging with Ar for 5 s. A total of 200 times are completed for film deposition, and the film thickness is 20 nm;

[0153] (5) Electrode preparation: The IZO electrode was prepared by sputtering. A 13.56 MHz radio frequency power supply was used, with a deposition power of 100 W. During the sputtering process, 60 sccm of Ar and 5 sccm of O2 / Ar were introduced. The sputtering time was 30 min, and the film thickness was 70 nm.

[0154] Comparative Example 2

[0155] The Cu2O thin film battery was prepared by the following steps:

[0156] (1) The 2.5 cm × 2.5 cm FTO substrate was ultrasonically cleaned successively with acetone, absolute ethanol, and deionized water for 10 - 20 min, and dried with nitrogen at room temperature.

[0157] (2) Nitrogen-doped Cu2O was prepared by an electrochemical deposition process as the hole transport layer of the thin film solar cell, with a film thickness of 20 nm. Subsequently, an undoped Cu2O thin film with a thickness of 10 nm was deposited.

[0158] (3) By an electrochemical deposition method, a 1.2 μm thick Cu2O thin film was deposited as the light absorption layer at 40 °C.

[0159] (4) Electron transport layer deposition: The gallium oxide layer was prepared using an ALD device. Trimethylgallium (TMGa) was used as the gallium source, water was used as the oxygen source, and Ar gas was used as the carrier gas. An alternating pulse deposition growth mode was adopted. One deposition cycle consisted of four processes: introducing the TMGa source for 0.1 s; Ar purge for 5 s; introducing H2O gas for 20 s; and finally Ar purge for 5 s. A total of 200 times were completed for film deposition, and the film thickness was 20 nm.

[0160] (5) Electrode preparation: The IZO electrode was prepared by sputtering. A 13.56 MHz radio frequency power supply was used, with a deposition power of 100 W. During the sputtering process, 60 sccm of Ar and 5 sccm of O2 / Ar were introduced. The sputtering time was 30 min, and the film thickness was 70 nm.

[0161] Comparative Example 3

[0162] The Cu2O thin film battery was prepared by the following steps:

[0163] (1) Substrate cleaning: The 2.5 cm × 2.5 cm FTO substrate was ultrasonically cleaned successively with acetone, absolute ethanol, and deionized water for 10 - 20 min, and dried with nitrogen at room temperature.

[0164] (2) Hole transport layer deposition: p-type Sb:SnO2 was prepared using a sputtering device, and the target was an Sb-doped SnO2 target (Sb2O3:SnO2 = 2:8); a 13.56 MHz RF power supply was used, the deposition power was 100 W, 60 sccm of Ar and 3 sccm of O2 were introduced during sputtering. The sputtering time was 30 min, and the film thickness was 100 nm;

[0165] (3) Nitrogen-doped cuprous oxide deposition: N-doped Cu2O thin films were prepared by reactive sputtering without substrate heating. The film-forming conditions are described as follows. Target: Cu (5N, 75 mm φ) Pressure during film formation: 0.7 Pa Gas flow during film formation: Ar / O2 / N2 = 85 / 15 / 15 (sccm) Power during film formation: 150 W, Film formation time: 30 minutes;

[0166] (4) Electron transport layer deposition: A gallium oxide layer was prepared using an ALD device, trimethylgallium (TMGa) as the gallium source, water as the oxygen source, and Ar gas as the carrier gas. An alternating pulse deposition growth mode was adopted, and one deposition cycle consisted of four processes: introducing the TMGa source for 0.1 s; Ar purge for 5 s; introducing H2O gas for 20 s; and finally Ar purge for 5 s. A total of 200 times were completed for film deposition, and the film thickness was 20 nm;

[0167] (5) Electrode preparation: IZO electrodes were prepared by sputtering. A 13.56 MHz RF power supply was used, the deposition power was 100 W, 60 sccm of Ar and 5 sccm of O2 / Ar were introduced during sputtering. The sputtering time was 30 min, and the film thickness was 70 nm.

[0168] Experimental example: Performance detection experiment of battery samples

[0169] The following experiments were carried out on the battery samples prepared by the methods of the above Examples 1-3 and Comparative Examples 1-4 to detect their various battery performances.

[0170] (1) Electrical performance test: The contact resistivity and sheet resistance of each battery sample were tested using the TLM test method, and parameters such as fill factor, conversion efficiency, and open-circuit voltage were measured using an IV tester.

[0171] (2) Transmittance test: The transmittance of each battery sample was tested using a spectrophotometer.

[0172] The main process parameters of the Examples and Comparative Examples and the performance detection experiment results of the Experimental Example are shown in Table 1.

[0173] Table 1

[0174]

[0175] Summary: Examples 1-3 show that there are significant improvements in their fill factor, short-circuit current, and open-circuit voltage, indicating that the technical solution of this application can effectively promote the transport of holes to the back electrode, prevent the transport of electrons to the back electrode, and thus inhibit the recombination of electrons and holes on the back surface. At the same time, the hole carrier concentration also increases significantly. An increase in the hole concentration can result in a higher material conductivity. This also shows that the technical solution of this application can improve the hole carrier extraction efficiency of cuprous oxide solar cells, reduce the hole contact resistance at the back interface, and reduce the recombination of minority carriers on the back surface, thereby improving the photovoltaic performance of the material.

[0176] Although the embodiments of this application have been described above, this application is not limited to the above specific embodiments and application fields. The above specific embodiments are merely illustrative and guiding, rather than restrictive. Those of ordinary skill in the art can also make many forms under the inspiration of this specification and without departing from the scope protected by the claims of this application, and these all fall within the scope claimed by this application.

Claims

1. A method for preparing a cuprous oxide thin film battery, wherein, It includes the following steps: Substrate preparation; Electron transport layer preparation, which includes forming an electron transport layer thin film on the substrate; Light-absorbing layer preparation, which includes forming a cuprous oxide thin film on the electron transport layer; Light-absorbing layer doping, which includes doping the cuprous oxide thin film with group V elements; Hole transport layer preparation, which includes forming a hole transport layer on the doped cuprous oxide thin film; Electrode preparation, which includes preparing an electrode on the hole transport layer.

2. The preparation method according to claim 1, wherein, The electron transport layer and hole transport layer are prepared by ALD, PVD or PEALD methods.

3. The preparation method according to claim 1, wherein The electron transport layer material is selected from gallium oxide, titanium oxide, zinc oxide or tin oxide, and / or the hole transport layer material is selected from tin oxide, preferably antimony-doped tin oxide.

4. The preparation method according to claim 1, wherein, The light-absorbing layer preparation includes using a copper target as a target and depositing a cuprous oxide thin film with a thickness of 800 nm - 5 μm by magnetron sputtering.

5. The preparation method according to claim 1, wherein The light-absorbing layer doping is carried out by doping group V elements on the surface of the cuprous oxide thin film away from the electron transport layer side. Preferably, the percentage of the doping depth in the thickness of the cuprous oxide thin film during doping is 20 - 50%.

6. The preparation method according to any one of claims 1-5, wherein, The light-absorbing layer doping includes doping group V elements by thermal diffusion.

7. The preparation method according to claim 6, wherein, The thermal diffusion includes gas thermal diffusion or chemical solution immersion thermal diffusion; Preferably, nitrogen or phosphorus element doping is carried out by the gas thermal diffusion; or Arsenic, antimony or bismuth element doping is carried out by the chemical solution immersion thermal diffusion.

8. The preparation method according to claim 7, wherein, When carrying out nitrogen element doping by the gas thermal diffusion, the flow rate of the doped nitrogen is 30 - 180 sccm, and the doping concentration is 0.1 at% - 20 at%.

9. The preparation method according to claim 7, wherein, When carrying out phosphorus element doping by the gas thermal diffusion, 50 - 300 mg of phosphorus powder forms phosphorus vapor to react with the cuprous oxide thin film.

10. The preparation method according to claim 8 or 9, wherein, During the doping reaction process, argon with a flow rate of 80 sccm is added as a carrier gas, and the argon pressure is maintained at 100 - 400 Pa during the reaction.

11. According to the preparation method described in claim 10, wherein, The diffusion temperature of the doping reaction is 200 - 600 °C, and the diffusion time is 30 - 85 min.

12. The preparation method according to claim 7, wherein, When carrying out arsenic, antimony or bismuth element doping by the chemical solution immersion thermal diffusion, the cuprous oxide thin film is immersed in an arsenic source, antimony source or bismuth source solution, and after contact and reaction, annealing is carried out.

13. According to the preparation method described in claim 12, wherein, The arsenic source solution is a 0.2 - 2 M arsenic nitrate solution, the antimony source solution is a 0.01 - 0.2 M potassium antimonyl tartrate solution, and the bismuth source solution is a 0.2 - 2 M bismuth nitrate solution.

14. The preparation method according to claim 12, wherein, The reaction time is 10 s - 10 min.

15. The preparation method according to claim 12, wherein The annealing temperature is 200 - 500 °C, and the annealing time is 30 s - 20 min.

16. The preparation method according to claim 1, wherein, The electrode preparation includes preparing a conductive electrode by magnetron sputtering or ALD method, and the electrode is selected from IZO, ITO, IWO, ITiO or AZO.

17. A cuprous oxide thin film battery, the battery comprising: A substrate, an electron transport layer, a cuprous oxide light-absorbing layer, a hole transport layer and an electrode are arranged in sequence, wherein the cuprous oxide light-absorbing layer is doped with group V elements.

18. The cuprous oxide thin film battery according to claim 17, wherein, Part of the area of the cuprous oxide light-absorbing layer close to the hole transport layer side is doped with group V elements. Preferably, the percentage of the doping depth in the thickness of the cuprous oxide light-absorbing layer is 20 - 50%.

19. The cuprous oxide thin film battery according to claim 17 or 18, wherein, The thickness of the electron transport layer is 5 - 50 nm, the thickness of the cuprous oxide light-absorbing layer is 800 nm to 5 μm, and the thickness of the hole transport layer is 5 nm - 200 nm.

20. The cuprous oxide thin film battery according to claim 19, wherein, The electron transport layer material is selected from gallium oxide, titanium oxide, zinc oxide or tin oxide, preferably gallium oxide, and the hole transport layer material is selected from tin oxide, preferably antimony-doped tin oxide.

21. The cuprous oxide thin film battery according to any one of claims 17 to 20, which is prepared by the preparation method according to any one of claims 1 to 16.